7 ft d 02180 900 radians then dh 45 a z

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ection 13.4) that (r (t) × r (t)) × r (t) = r (t) × r (t) r (t) , and the result follows. (c) From Exercise 39 of Section 13.4, (r (t) × r (t)) × r (t) = r (t) 2 r (t) − (r (t) · r (t))r (t) = u(t), so N(t) = u(t)/ u(t) 505 Chapter 14 1 2 22. (a) r (t) = 2ti + j, r (1) = 2i + j, r (t) = 2i, u = 2i − 4j, N = √ i − √ j 5 5 π (b) r (t) = −4 sin ti + 4 cos tj + k, r ( ) = −4i + k, r (t) = −4 cos ti − 4 sin tj, 2 π r ( ) = −4j, u = 17(−4j), N = −j 2 23. r (t) = cos ti − sin tj + k, r (t) = − sin ti − cos tj, u = −2(sin ti +cos tj), u = 2, N = − sin ti − cos tj 24. r (t) = i + 2tj + 3t2 k, r (t) = 2j + 6tk, u(t) = −(4t + 18t3 )i + (2 − 18t4 )j + (6t + 12t3 )k, 1 N= √ −(4t + 18t3 )i + (2 − 18t4 )j + (6t + 12t3 )k 2 81t8 + 117t6 + 54t4 + 13t2 + 1 EXERCISE SET 14.5 1. κ ≈ 1 =2 0.5 2. κ ≈ 1 3 = 4/3 4 3. r (t) = 2ti + 3t2 j, r (t) = 2i + 6tj, κ = r (t) × r (t) / r (t) 3 = 6 t(4 + 9t2 )3/2 4. r (t) = −4 sin ti+cos tj, r (t) = −4 cos ti−sin tj, κ = r (t)×r (t) / r (t) 5. r (t) = 3e3t i − e−t j, r (t) = 9e3t i + e−t j, κ = r (t) × r (t) / r (t) 3 = 6. r (t) = −3t2 i + (1 − 2t)j, r (t) = −6ti − 2j, κ = r (t) × r (t) / r (t) 3 3 = 4 (16 sin t + cos2 t)3/2 2 12e2t 3/2 (9e6t + e−2t ) = 6 t2 (t − 1)2 (9t4 + 4t2 − 4t + 1)3/2 7. r (t) = −4 sin ti + 4 cos tj + k, r (t) = −4 cos ti − 4 sin tj, κ = r (t) × r (t) / r (t) 3 = 4/17 √ 8. r (t) = i + tj + t k, r (t) = j + 2tk, κ = r (t) × r (t) / r (t) 2 3 = t4 + 4t2 + 1 (t4 + t2 + 1)3/2 9. r (t) = sinh ti + cosh tj + k, r (t) = cosh ti + sinh tj, κ = r (t) × r (t) / r (t) 10. r (t) = j + 2tk, r (t) = 2k, κ = r (t) × r (t) / r (t) 3 = 3 = 2 (4t2 + 1)3/2 11. r (t) = −3 sin ti + 4 cos tj + k, r (t) = −3 cos ti − 4 sin tj, r (π/2) = −3i + k, r (π/2) = −4j; κ = 4i + 12k / − 3i + k 12. r (t) = et i − e−t j + k, r (t) = et i + e−t j, r (0) = i − j + k, r (0) = i + j; κ = − i + j + 2k / i − j + k 3 = 2/5, ρ = 5/2 3 = √ √ 2/3, ρ = 3/ 2 13. r (t) = et (cos t − sin t)i + et (cos t + sin t)j + et k, r (t) = −2et sin ti + 2et cos tj + et k, r (0) = i + j + k, √ √ r (0) = 2j + k; κ = − i − j + 2k / i + j + k 3 = 2/3, ρ = 3 2/2 1 2 cosh2 t Exercise Set 14.5 506 14. r (t) = cos ti − sin tj + tk, r (t) = − sin ti − cos tj + k, √ √ r (0) = i, r (0) = −j + k; κ = − j − k / i 3 = 2, ρ = 2/2 √ s 1 s 1 3 i − sin 1 + j+ k, r (s) = 1, so 15. r (s) = cos 1 + 2 2 2 2 2 1 s 1 s dT 1 dT = − sin 1 + i − cos 1 + j, κ = = ds 4 2 4 2 ds 16 16. r (s) = − 3 − 2s si + 3 2s j, r (s) = 1, so 3 1 1 dT dT i + √ j, κ = =√ = ds ds 9 − 6s 6s 1 1 + = 9 − 6s 6s 17. (a) r = x i + y j, r = x i + y j, r × r 3 2s(9 − 6s) = |x y − x y |, κ = |x y − y x | (x 2 + y 2 )3/2 (b) r = xi + y (x)j, r (x) = i + (dy/dx)j, r (x) = (d2 y/dx2 )j, so κ(x) = (d2 y/dx2 )k / i + (dy/dx)j 18. 3 = |d2 y/dx2 |/[1 + (dy/dx)2 ]3/2 . dy |y | = tan φ, (1 + tan2 φ)3/2 = (sec2 φ)3/2 = | sec φ|3 , κ(x) = = |y cos3 φ| dx | sec φ|3 19. κ(x) = | sin x| , κ(π/2) = 1 (1 + cos2 x)3/2 20. κ(x) = 2|x| , κ(0) = 0 (1 + x4 )3/2 21. κ(x) = √ 2|x|3 , κ(1) = 1/ 2 4 + 1)3/2 (x 22. κ(x) = e−x e−1 , κ(1) = (1 + e−2x )3/2 (1 + e−2 )3/2 23. κ(x) = √ 2 sec2 x| tan x| , κ(π/4) = 4/(5 5) 4 x)3/2 (1 + sec 24. By implicit differentiation, dy/dx = 4x/y , d2 y/dx2 = 36/y 3 so κ = if (x, y ) = (2, 5) then κ = 36/125 36 =√ (1 + 64/25)3/2 89 89 25. x (t) = 2t, y (t) = 3t2 , x (t) = 2, y (t) = 6t, x (1/2) = 1, y (1/2) = 3/4, x (1/2) = 2, y (1/2) = 3; κ = 96/125 26. x (t) = −4 sin t, y (t) = cos t, x (t) = −4 cos t, y (t) = − sin t, x (π/2) = −4, y (π/2) = 0, x (π/2) = 0, y (π/2) = −1; κ = 1/16 27. x (t) = 3e3t , y (t) = −e−t , x (t) = 9e3t , y (t) = e−t , √ x (0) = 3, y (0) = −1, x (0) = 9, y (0) = 1; κ = 6/(5 10) 28. x (t) = −3t2 , y (t) = 1 − 2t, x (t) = −6t, y (t) = −2, x (1) = −3, y (1) = −1, x (1) = −6, y (1) = −2; κ = 0 36/|y |3 ; (1 + 16x2 /y 2 )3/2 507 Chapter 14 29. x (t) = 1, y (t) = −1/t2 , x (t) = 0, y (t) = 2/t3 √ x (1) = 1, y (1) = −1, x (1) = 0, y (1) = 2; κ = 1/ 2 30. x (t) = 4 cos 2t, y (t) = 3 cos t, x (t) = −8 sin 2t, y (t) = −3 sin t, x (π/2) = −4, y (π/2) = 0, x (π/2) = 0, y (π/2) = −3, κ = 12/43/2 = 3/2 31. (a) κ(x) = ρ(x) = | cos x| , (1 + sin2 x)3/2 (b) κ(t) = (1 + sin2 x)3/2 | cos x| ρ(t) = 2 , (4 sin2 t + cos2 t)3/2 1 (4 sin2 t + cos2 t)3/2 , 2 ρ(0) = 1/2, ρ(π/2) = 4 ρ(0) = ρ(π ) = 1. y y c r (0) = r (c) = 1 x 1 ρ 6 =4 () x 2 1 ρ (0) = 2 32. x (t) = −e−t (cos t + sin t), κ −t y (t) = e (cos t − sin t), −t x (t) = 2e sin t, −t y (t) = −2e 6 cos t; using the formula of Exercise 17(a), 1 κ = √ et . 2 t -3 3 33. (a) At x = 0 the curvature of I has a large value, yet the value of II there is zero, so II is not the curvature of I; hence I is the curvature of II. (b) I has points of inflection where the curvature is zero, but II is not zero there, and hence is not the curvature of I; so I is the curvat...
View Full Document

Ask a homework question - tutors are online